Probing into the Interaction of Nicotine and Bovine Submaxillary Mucin: NMR, Fluorescence, and FTIR Approaches - Xiaoxiang Liao; Dalin Yuan; Jianguo Tang; Hongqin Yang; Bing Liang; Qiang Cheng; Hui Li (Journal of Spectroscopy)
Nicotine, the important component of cigarette products, may have an impact on the oral environment after inhalation. The research of interaction between nicotine and bovine submaxillary mucin (BSM) contributes to understand the binding mechanism of nicotine and BSM, and the effects of nicotine on the structure and function of the mucin. NMR data demonstrated that the interaction between nicotine and BSM did exist, and it was pyrrolidyl ring of nicotine playing the major role in the binding. The quenching mechanisms of nicotine and BSM in different pH were different: for acidic environment, the quenching was dynamic; while it became static in the alkaline circumstance. Synchronous fluorescence spectra indicated that nicotine had effect on the microenvironment of the Trp rather than Tyr residue. Meanwhile, the impact of nicotine on the conformation of BSM was also confirmed by 3D fluorescence and FTIR spectra.